Torta de amêndoa de dendê: consumo, digestibilidade, metabolismo ruminal e desempenho leiteiro em bubalinos - Natalia Guarino Souza Barbosa (2010)
The palm kernel cake (PKC) is the main agricultural byproduct available for animal feed in Para State, Brazil. Studies were conducted to visualize factors affecting industrial standardization as well as to determine best level of inclusion, metabolism and performance of buffaloes fed with PKC. There are industrial stages that affect the quality of the finalproduct. Seven studies in a randomized block design were performed to assess the effects of increasing levels of PKC (0, 20, 40 and 60%) at buffaloes´ diets as the following sequence: 1- Intake of dry matter (DM), Neutral Detergent Fiber (NDF), ether extract (EE) and crude protein (CP), digestible energy (DE), 2 - Apparent digestibility (DM, CP, and Crude Energy-CE) and true digestibility (NDF), 3 - Rate of passage of solids, 4 - In situ degradability (DM, NDF, ADF and CP), 5 - rumen environment (pH, production of volatile fatty acids and ammonia nitrogen-NH3), 6- Rumen emptying, with total rumen volume estimated by the balls method, created at current study and 7 - Determination of total protozoa population. Fourcrossbred buffaloes (initial weight ± 380.10 Kg) were tested at studies 1 and 2. Consumption (g/Kg0.75/day) ranged from 50.12 to 64.48, from 38.56 to 57.79, 2.58 to 3.52 and from 5.78 to 8.53 for DM, NDF, EE and CP respectively and CE (Kcal/kg0.75/day) from 108.18 to 180.15.Apparent digestibility (%) ranged from 46.44 to 58, from 50.68 to 62.75, from 46.81 to 60.60, from 68.43 to 88.72 and from 42.94 to 50.99 to DM, NDF, EB, CE and CP, respectively. Studies 3-7 were conducted with three rumen fistulated buffaloes. The passage rate was approximately 2% per hour. Effective degradability, potential and rate of degradation ofsilage and PKC were higher for PKC in relation to silage, highlighting the quality of its fiber. Rumen pH was suitable in all four levels of PKC inclusion, with an average of 6.82. The concentrations of ammonia nitrogen were adequate up to 40% of PKC. The average ratio ofacetate: propionate: butyrate was 68:26:6 (100% silage) and 75:20:5 (60% PKC). The inclusion of PKC in the diet decreased the solid fraction of the digesta until 40% of PKC. There was an increase of gas fraction with increasing addition of PKC. The method of balls proved to be practical and useful, especially as a screening of more sophisticated equipments. The protozoa population decreased as PKC increased. The best level of PKC, in all seven studies, was 60% of inclusion. Dairy performance study with female buffaloes receiving 60% of PKC was conducted. The addition of PKC was effective (p <0.05) to increase the content of fat, total solids and conjugated linoleic acid in buffaloes´ milk, with no difference in milk yield (P> 0.05). The conclusion of current studies is that PKC has characteristics of bulk food, and that it can replace this fraction in ruminant´s feed with superiorities over elephant grass silage, with increases in milk quality, particularly for CLA, which increased 44 %.